2007
DOI: 10.1021/jp075452d
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Determination of the Positions of the Copper Cations in Zeolite MFI

Abstract: Copper-exchanged Cu-MFI (Cu-ZSM-5) materials have been prepared by reacting H-MFI samples with 0.1 M Cu(II) acetate solutions. Interpretation (Rietveld method) of X-ray powder diffraction (XRPD) profiles corresponding to two fully dehydrated Cu-MFI phases, reveals the presence of several independent extra framework Cu centers. In H 1.04 Cu(I) 1.19 Cu(II) 0.51 MFI and H 1.99 Cu(I) 2.37 Cu(II) 0.00 MFI, four and five Cu cations are located, respectively. In these two phases, the Cu1/Cu2/Cu2′/Cu3/Cu3′ populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 36 publications
5
71
0
Order By: Relevance
“…4B). This placement is also consistent with the crystal structure of Cu I -ZSM-5, which resolves two Cu I atoms in the 10-membered ring separated by two intermediate T-sites (28). Thus, a larger model was formed with each Al T-site ligand extended with covalently bonded Si T-sites (Fig.…”
Section: Geometric and Electronic Structure Of The Cu2o Core In Cu-zssupporting
confidence: 85%
See 1 more Smart Citation
“…4B). This placement is also consistent with the crystal structure of Cu I -ZSM-5, which resolves two Cu I atoms in the 10-membered ring separated by two intermediate T-sites (28). Thus, a larger model was formed with each Al T-site ligand extended with covalently bonded Si T-sites (Fig.…”
Section: Geometric and Electronic Structure Of The Cu2o Core In Cu-zssupporting
confidence: 85%
“…This can result in an active core containing either two Cu III s or two Cu II s with an accompanying 2-electron transfer from nearby Cu I ions to reduce the additional O atom. ‡ In ZSM-5, the 10-membered rings of the lattice are the only sites with pore-sizes appropriate for access of O 2 , N 2 O, and CH 4, and within these rings, a Cu 2 O core could only bind two lattice Os to each Cu (28). We therefore initially modeled the site with a tetrahedral Al(OH) 4 (Fig.…”
Section: Geometric and Electronic Structure Of The Cu2o Core In Cu-zsmentioning
confidence: 99%
“…A recent study by Fickel et al using Rietveld refinement of synchrotron-based powder X-ray diffraction (XRD) data revealed an exclusive occupation of Cu 2+ cations in the plane of the six-ring that comprise each end of the double six membered ring (d6r) subunits of SSZ-13 (CHA structure) [6,7]; in comparison Cu-ZSM-5 is known to possess 5 cationic positions for Cu 2+ within its framework [8]. EXAFS data further revealed that the Cu 2+ ions do not sit in the center of the plane of the six-ring but rather tend to be displaced towards the edge of the ring in a 3-4 coordinate planar arrangement [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, catalytic active metal sites have been extensively studied by various methods such as synchrotron powder X-ray diffraction (XRD), X-ray absorption fine structure, theoretical modeling, and others [1][2][3][4][5][6][7]. Especially, some ZSM-5 and ferrierite structures including non-framework cation positions have been determined by powder XRD [5,6,8,9]. Although theoretical studies for NO in Fe-exchanged ferrierite provided some useful but indirect information about NO and Fe interactions [3], the detailed structures and environments of transition metals and adsorbed molecules including reactants and intermediates in metal exchanged ZSM-5 and ferrierite have been rarely confirmed due to some limitations on the analytical methods and materials.…”
Section: Introductionmentioning
confidence: 99%